FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENYALAHGUNAAN NAPZA (NARKOTIKA, PSIKOTROPIKA DAN ZAT ADIKTIF) PADA REMAJA DI WILAYAH “X” KOTA PADANG 2017 - Miswarti - (Menara Ilmu, 2018)
Teenagers today are very worrying because it has been a lot of irregularities inteenagers one abuse of drugs. It is a substance which poses a particular influence to his user'senter into the body. The purpose of this research is to know the factors that are associated withthe abuse of drugs (narcotics, psychotropic drugs, and addictive substances) in the area of "X"Padang city 2017Type of this research is quantitative design with cross sectional study. This researchhas been done on the March to October in relic in an "X" in the year 2017. The number ofpopulation in the study 30 people, sampling by means of accidental sampling.The results of this research show that there is a meaningful relationship between thepersonality with the abuse of DRUGS (84.2%), there is a meaningful relationship betweenfamilies with abuse of DRUGS (80.0%), there is a meaningful relationship between the peerswith the abuse of DRUGS (83.3%)Expected to community social institution in the "X" city of padang to make programsthat may prevent his going to abuse DRUGS among teenagers one by holding the extensionextensionof DRUGS so that the understand more about the teens who USE DRUGS, thedangers of DRUGS and the penalties for the misuse of DRUGS so that teenagers can stopusing DRUGS.